Exploring the Effects of Organizational Structure Variables on the Organizational Justice Perceptions of Correctional Staff - Lambert, Eric G. (The prison journal, 2021)
Research examining the effect of organizational justice on the correctional environment is typically limited to its consequences on various outcomes. Absent from this body of literature is how perceptions of organizational justice are formed among correctional staff. Filling this void and using data from a Midwestern correctional facility, the current study examines the impact of instrumental communication, integration, formalization, and input into decision-making on the distributive and procedural justice perceptions of correctional staff. With the exception of integration, all organizational structure variables were significantly related to both forms of organizational justice. These findings offer correctional administrators a low cost and practical solution for enhancing organizational justice through organizational structure.